HCS08 Unleashed : Designer´s guide to the HCS08 microcontrollers - Pereira, Fábio ([s.n.], 2009)
Introduction - The HCS08 architecture - The codewarrior IDE - The C programming language - System modules - Input/output ports - Clocking system - Low power modes - Timing peripherals - Analog peripherals - Communication peripherals - FLASH memory controller - Project examples - HCS08 instruction set - ASCII table.